Application of Cultural Capital to Create Thai Phuan Dance Performance: An Approach to Promote the Health of the Elderly in the Community - Rittibul, Pravit; Nasom, Chananchida; Boontonglek, Manoch; Pummarak, Sipapa; Naksukhum, Supawadee (Journal of Posthumanism, 2025)
This research explores using community cultural capital to develop a Thai Phuan dance performance for elderly health promotion in Prachin Buri. Twenty informants, including local scholars, artists, and community leaders, were purposively selected. Data was collected through interviews, observation, and performance analysis, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The performance design integrated local Thai Phuan arts and culture, maintaining traditional melodies for familiarity while incorporating Lam Nam songs to enhance communication and evoke emotions. New lyrics raise awareness about stress reduction and muscle strengthening for the elderly. Movements blend Northeastern folk dance with music-related independent actions, incorporating recreation and exercise principles in warm-up, exercise, and cool-down phases.